Can seawater desalination be a win-win fix to our water cycle?. (1st September 2020) - Pistocchi, A.; Bleninger, T.; Breyer, C.; Caldera, U.; Dorati, C.; Ganora, D.; Millán, M.M.; Paton, C.; Poullis, D.; Herrero, F. Salas; Sapiano, M.; Semiat, R.; et al.
Abstract: While we increasingly turn to desalination as a secure water supply, it is still perceived as an expensive and environmentally damaging solution, affordable only for affluent societies. In this contribution, we recast desalination from one of a last resort to a far-reaching, climate change mitigating, water security solution. First, we argue that the benefits of desalination go beyond the single-use value of the water produced. If coupled with water reuse for irrigation, desalination reduces groundwater abstraction and augments the water cycle. As such, it may support both adaptation to, and mitigation of climate change impacts by deploying plentiful water for human use, with all the benefits that entails, while helping preserve and restore ecosystems. Second, we counter two arguments commonly raised against desalination, namely its environmental impact and high cost. The environmental impact can be fully controlled so as not to pose long-term threats, if driven by renewable energy. Desalination may then have a zero carbon footprint. Moreover, appropriately designed outfalls make the disposal of brine at sea compatible with marine ecosystems.. Recovery of energy, minerals and more water from brine reject (particularly in the form of vapour for cooling to enable more crops and vegetation to grow), while possible, is often hardly economically justified. However, resource recovery may become more attractive in the future, and help reduce the brine volumes to dispose of. When fresh water becomes scarce, its cost tends to go up, making desalination increasingly economic. Moreover, desalination can have virtually no environmental costs. Considering the environmental costs of over-abstraction of freshwater, desalination tilts the balance in its favour. Highlights: Here we recast desalination as a "win-win solution" to restore the water cycle. Desalination to become mainstream as societies understand its broader benefits. Coupling with water reuse maximizes socioeconomic/ecological return on investments.